Emergency ambulance transport induces stress in patients with acute coronary syndrome. Issue 7 (22nd June 2009) - Weber, U; Reitinger, A; Szusz, R; Hellmich, C; Steinlechner, B; Hager, H; Mora, B; Selzer, M; Hiesmayr, M; Kober, A
Abstract : Background: Trials with healthy volunteers have shown that emergency ambulance transportation induces stress, which becomes evident by an increase in heart rate, blood pressure and plasma levels of stress hormones such as adrenaline, noradrenaline, cortisol and prolactin. A study was undertaken to test the hypothesis that emergency ambulance transportation may also lead to stress in patients with acute coronary syndrome. Methods: Venous plasma levels of epinephrine, norepinephrine and lactate as well as visual analogue scale (VAS) scores for pain and anxiety were measured in 32 patients with defined clinical signs of acute coronary syndrome before and after transportation. Heart rate, blood pressure and transcutaneous oxygen saturation levels were recorded every 3 min. Results: Mean (SD) plasma levels of epinephrine and norepinephrine increased significantly (p<0.01) during transportation (159.29 (55.34) ng/l and 632.53 (156.32) ng/l before transportation vs 211.03 (70.12) ng/l and 782.93 (173.95) ng/l after transportation), while lactate levels, heart rate and mean blood pressure remained almost stable. There was no significant change in mean (SD) VAS scores for pain and anxiety (3.79 (3.70) and 2.89 (3.01) vs 2.13 (3.30) and 1.57 (2.78)). Conclusion: Emergency ambulance transportation induces a rise in plasma catecholamine levels and therefore stress in patients with acute coronary syndrome, but does not result in cardiac shock as lactate levels and haemodynamic parameters remain normal.